Cancer Cachexia - Del Fabbro, Egidio; Inui, Akio; Strasser, Florian (Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2012)
Cancer Cachexia is a concise, fully illustrated handbook written with the aim of increasing awareness of cancer cachexia and highlighting best practice diagnosis, treatment, and management options for this devastating disorder. This is another title in the ongoing Springer Healthcare Cancer Supportive Care Series.